2009
DOI: 10.1177/0741932509355988
|View full text |Cite
|
Sign up to set email alerts
|

Reading Comprehension Instruction for Students With Learning Disabilities, 1995—2006: A Meta-Analysis

Abstract: Meta-analysis procedures were employed to synthesize findings of research for improving reading comprehension of students with learning disabilities published in the decade following previous meta-analytic investigations. Forty studies, published between 1995 and 2006, were identified and coded. Nearly 2,000 students served as participants. Interventions were classified as fundamental reading skills instruction, text enhancements, and questioning/strategy instruction—including those that incorporated peer-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
116
2
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(139 citation statements)
references
References 50 publications
12
116
2
9
Order By: Relevance
“…Les conclusions de leur synthèse précisent que l'enseignement explicite des stratégies est l'intervention ayant le plus d'effets positifs sur la compréhension de ces élèves en lecture. Deux méta-analyses portant sur les interventions en compréhension de lecture auprès des élèves éprouvant des difficultés (Sencibaugh, 2007;Berkeley, Scruggs & Mastropieri, 2010) (Archer & Hugues, 2011). Cette approche permet aux élèves plus forts de passer plus rapidement à l'étape du travail autonome alors que les autres élèves peuvent bénéficier de soutien supplémentaire (Juel & Minden-Cup, 2000).…”
Section: L'importance De Comprendre Les Textes Courantsunclassified
“…Les conclusions de leur synthèse précisent que l'enseignement explicite des stratégies est l'intervention ayant le plus d'effets positifs sur la compréhension de ces élèves en lecture. Deux méta-analyses portant sur les interventions en compréhension de lecture auprès des élèves éprouvant des difficultés (Sencibaugh, 2007;Berkeley, Scruggs & Mastropieri, 2010) (Archer & Hugues, 2011). Cette approche permet aux élèves plus forts de passer plus rapidement à l'étape du travail autonome alors que les autres élèves peuvent bénéficier de soutien supplémentaire (Juel & Minden-Cup, 2000).…”
Section: L'importance De Comprendre Les Textes Courantsunclassified
“…This is not surprising, since secondary teachers often will try to make instruction less difficult for students with LD by implementing these types of activities [65]. Teachers in the study were observed using more effective instructional practices such as questioning, activating prior knowledge, and using graphic organizers with some frequency [19]. Teachers also exposed students to several reading comprehension strategies such as summarizing, annotating, and previewing, but explicit instruction in how and when to use reading comprehension strategies was not observed nor did they provide students with opportunities to practice using the strategies independently.…”
Section: Discussionmentioning
confidence: 84%
“…A critical component of effective questioning for comprehension; however, includes assisting students in becoming independent at self-questioning while reading. This includes teaching students how to generate and answer their own questions about text and providing students with strategies for what to do when they cannot answer a question [19]. Although teachers asked students a number of text-based questions, teachers did not provide students with instruction on how to generate their own questions or what to do if they could not answer teacher-generated questions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La lecture répétée de textes, avec modelage et rétroaction, est aussi un moyen efficace d'améliorer la fluidité en lecture de texte, en particulier chez les élèves du primaire (Lee et Yoon, 2016). Enfin, l'enseignement explicite de stratégies de compréhension qui conduisent les lecteurs en difficulté à accorder une attention particulière au sens véhiculé par le texte, telles que l'identification de l'idée principale et la synthèse, conduit à une amélioration significative de leur performance en lecture (Berkeley, Scruggs, et Mastropieri, 2010;Solis, Ciullo, Vaughn, Pyle, Hassaram et Leroux, 2012).…”
Section: L'intensification Des Interventions Aux Paliers II Et Iiiunclassified